111 The impact of introducing national policies of improving working conditions on overwork-related cardiovascular mortality in taiwan. (24th April 2018) - Lin, Ro-Ting
Abstract : Introduction: Cardiovascular diseases (CVDs) are the leading cause of death globally. Occupational related risk factors for CVD incidence and mortality include long working hours, high job stress, and low employment opportunities. 'Overwork' or ' Karoshi ' has since been a major occupational health concern for Asian workers. In response to public's worries of long working hours and low salary in Taiwan, Taiwanese government vigorously amended standard working hours, holiday, and basic salary under the Labour Standard Act and the criteria to recognise overwork-related CVDs during 2015–2016. We investigated the ecological association among national policies, working conditions, and overwork-related CVDs. Methods: We collected data on the working conditions and overwork-related CVDs for each industry sector and identify the high-risk group. We estimated the combined effect of national policies and working conditions on overwork-related CVDs for each industry sector and further estimated the expected number of overwork-related CVDs to investigate the impact of introducing the new policies. We finally measured the extent of preventable CVDs for each industry sector as a result of introducing new policies and improving working conditions. Result: Our analysis covered 11.27 million workers from 17 industry sectors in Taiwan. We found consistent and plausible correlations between the implementation of new policies, the working conditions, and the number of recognised overwork-related CVDs. Compared to workers in the education sector, employees in the support service and manufacturing sectors had greater likelihoods of overwork-related CVDs. Such gap was particularly obvious in their monthly working hours by a difference of 50 hours per month. Discussion: In view of Taiwan's working environment, reducing working hours is the key element to reducing the burden of overwork-related CVDs. Our result can contribute to the government's decision-making process and society's understanding of preventable overwork-related CVDs in each industry sector by providing justification for proceeding to new policies.